Smoking-related cancer in military veterans: retrospective cohort study of 57, 000 veterans and 173, 000 matched non-veterans. Issue 1 (December 2016) - Bergman, Beverly; Mackay, Daniel; Morrison, David; Pell, Jill
Abstract Background Serving military personnel are more likely to smoke, and to smoke more heavily, than civilians. The aim of our study was to examine whether veterans have an increased risk of a range of smoking-related cancers compared with non-veterans, using a large, national cohort of veterans. Methods We conducted a retrospective cohort study of 57, 000 veterans resident in Scotland and 173, 000 age, sex and area of residence matched civilians. We used Cox proportional hazard models to compare the risk of any cancer, lung cancer and other smoking-related cancers overall, by sex and by birth cohort, adjusting for the potential confounding effect of socioeconomic deprivation. Results Over a mean of 29 years follow-up, 445 (0.79 %) veterans developed lung cancer compared with 1106 (0.64 %) non-veterans (adjusted hazard ratio 1.16, 95 % confidence intervals 1.04–1.30, p  = 0.008). Other smoking-related cancers occurred in 737 (1.31 %) veterans compared with 1883 (1.09 %) non-veterans (adjusted hazard ratio 1.18, 95 % confidence intervals 1.08–1.29, p  < 0.001). A significantly increased risk was observed among veterans born 1950–1954 for lung cancer and 1945–1954 for other smoking-related cancers. The risk of lung cancer was decreased among veterans born 1960 onwards. In comparison, there was no difference in the risk of any cancer overall (adjusted hazard ratio 0.98, 95 % confidence intervals 0.94–1.01, p  = 0.171), whilst younger veterans were at reduced risk of any cancer (adjusted hazard ratio 0.88, 95 % confidence intervals 0.81–0.97, p  = 0.006). Conclusions Military veterans living in Scotland who were born before 1955 are at increased risk of smoking-related cancer compared with non-veterans, but younger veterans are not. The differences may reflect changing patterns of smoking behaviour over time in military personnel which may, in turn, be linked to developments in military health promotion policy and a changing military operational environment, as well as to wider societal factors.